AN ANALYSIS ON WOMEN’S LANGUAGE FEATURE USED BY JACINDA ARDEN IN SPEECH ABOUT COVID-19 - Herman Herman; Vivi Lastiar Sinurat; Tiarma Intan Marpaung; Partohap Saut Raja Sihombing (Edu-Ling: Journal of English Education and Linguistics, 2021)
This study aims to find out women’s language feature used by Jacinda Arden in speech about COVID-19. The researchers conducted the study with Lakoff’s theory. This research investigates the type and function of women’s language in speech about COVID-19 used by Jacinda Arden. The research formulated a question as the problem “What are the women’s language feature used by Jacinda Arden in speech about COVID-19?” to find out the women’s language feature used by Jacinda Arden in speech about COVID-19. The researchers used qualitative research design by employing content analysis to answer the research question. There were 2 research instrument used in this research, they were the researchers as the human research and observation sheet. The researchers conducted the research by using the record and video script of Jacinda Arden in her speeches about COVID-19 that delivered on March 21 and April 6, 2020. The result of this study showed not all types of women’s language feature used Jacinda Arden. The researchers found seven types of women’s language feature. Those feature are divided into lexical hedges 18,15%, rising intonation 0,89%, empty adjectives 1,19%, intensifier 16,96, hypercorrect grammar 20,83%, super polite form 1,19%, and emphatic stress 40,77%. The absent women’s language features are tag question, price color term, and avoidance of using strong swear words. The most dominant women’s language feature is emphatic stress function of emphatic stress in this speech is to emphasize the main idea or word that she wanted to focus on.